Prospek Menuju Sekolah Adiwiyata Mandiri Sma Negeri Di Kabupaten Temanggung Tahun 2017 - Nisa, Lana Shofiatun; Setyowati, Dewi Liesnoor; Suharini, Erni (Jurusan Geografi, Fakultas Ilmu Sosial, Universitas Negeri Semarang, 2017)
This research aims to determine the preparation of the implementation of Adiwiyata Mandiri program in each school and to know high schoo that has the highest prospect to go to school Adiwiyata Mandiri. The results showed: SMA N 1 Temanggung 10 schools built and newly build 4 schools, SMA N 3 Temanggung and SMA N 1 Pringsurat not yet have a target school, SMA N 1 Candiroto has 10 schools built and has been built. The driving factors of coaching activities are good support from bebrapa parties and the environment, human resources meet, and school interest. Inhibiting factors are funding, too many required schools, distance, complicated administration. The prospect to go to Adiwiyata Mandiri's highest school is SMA N 1 Candiroto which is SMA N 1 Temanggung with the guidance activities which is done is general coaching, maintenance of school building 88.75% and 40%, construction of land use and school facilities 54, 43% and 20%, development of school extracurricular activities, creativity building and innovation of school residents 50% and 16.67%, development of environmental action activities conducted by outsiders such as making biopori, tree planting, construction of infrastructure facilities to overcome the problems The environment of 76% and 30%, the construction of infrastructure facilities to support environmental learning 53% and 22%, the maintenance of environmentally friendly school infrastructure facilities 97% and 40%, the improvement of the maintenance and maintenance of school sanitation facilities 90% and 40% Construction of electricity, water and ATK 80% and 40%, development of qualitative improvement As an environmentally friendly healthy canteen service 80% and 40%. Third and fourth is SMA N 3 Temanggung and SMA N 1 Pringsurat. Penelitian ini bertujuan untuk mengetahui persiapan pelaksanaan program Adiwiyata Mandiri pada masingmasing sekolah dan untuk mengetahui SMA Negeri yang memiliki prospek paling tinggi untuk menuju sekolah Adiwiyata Mandiri. Hasil penelitian menunjukkan: SMA N 1 Temanggung baru membina 4 sekolah, SMA N 3 Temanggung dan SMA N 1 Pringsurat belum memiliki sekolah binaan, SMA N 1 Candiroto sudah membina 10 sekolah. Faktor pendorong kegiatan pembinaan yaitu dukungan baik dari bebrapa pihak dan lingkungan, SDM memenuhi, dan ketertarikan sekolah. Faktor penghambatnya adalah dana, sekolah yang disyaratkan terlalu banyak, jarak,administrasi rumit. Prospek untuk menuju sekolah Adiwiyata Mandiri yang tertinggi adalah SMA N 1 Candiroto dalam kegiatan pembinaannya paling terendah adalah pembinaan dalam hal pembinaan pengembangan ekstrakulikuler sekolah yaitu 42%, sedangkan untuk yang paling tinggi adalah pembinaan dalam hal pemeliharaan sarana prasarana yang ramah lingkungan yaitu sebesar 97%. Kedua adalah SMA N 1 Temanggung, paling tinggi yaitu pada kegiatan pembinaan perawatan gedung sekolah, pemeliharaan sarana prasarana yang ramah lingkungan, peningkatan pengelolaan dan pemeliharaan fasilitas sanitasi sekolah, dan pemanfaatan listrik, air, dan ATK yaitu sebesar 40%. Ketiga dan keempat adalah SMA N 3 Temanggung dan SMA N 1 Pringsurat.